2018
DOI: 10.1007/s10508-018-1347-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Perceptions of Others’ Attitudes Toward Bisexual Men and Women Among a Nationally Representative Probability Sample

Abstract: Researchers posit that negative attitudes, prejudice, and discrimination (i.e., binegativity) from heterosexual and gay/lesbian individuals may contribute to health disparities among bisexual individuals relative to heterosexual and gay/lesbian individuals. Recent studies have focused on gay, lesbian, and heterosexual people’s (e.g., “others”) attitudes toward bisexual people. No studies have investigated how bisexual individuals perceive others’ attitudes toward bisexual people, which are generally known as “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The present study further revealed an association between the ISS dimension of identity and the sexual orientation of bisexuality in men, but not in women. Research has demonstrated that bisexual individuals experience prejudice, for example sexual orientation instability and sexual irresponsibility, from both heterosexuals and lesbians and gay men [ 66 , 67 , 68 ], which may increase the risk of developing ISS as part of a value system and in relation to identity [ 69 ]. The result indicated that the effect of social prejudice on internalizing stigma toward the sexual orientation of bisexuality might be stronger in men than in women.…”
Section: Discussionmentioning
confidence: 99%
“…The present study further revealed an association between the ISS dimension of identity and the sexual orientation of bisexuality in men, but not in women. Research has demonstrated that bisexual individuals experience prejudice, for example sexual orientation instability and sexual irresponsibility, from both heterosexuals and lesbians and gay men [ 66 , 67 , 68 ], which may increase the risk of developing ISS as part of a value system and in relation to identity [ 69 ]. The result indicated that the effect of social prejudice on internalizing stigma toward the sexual orientation of bisexuality might be stronger in men than in women.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, behavioral HIV prevention interventions tailored for MSMW are thin on the ground (13)(14)(15). PrEP may offer Black MSMW a wider-scale opportunity to receive efficacious HIV prevention, thereby lowering their risk for HIV acquisition and transmission and associated internalized bi-negativity (40), than existing behavioral interventions may offer them. Our results demonstrating that gay community support mediates the relationship between bisexual behavior and PrEP awareness among Black MSM provides additional confirmation for the value of sexual minority community support networks for public health promotion within sexual and gender minority communities.…”
Section: Discussionmentioning
confidence: 99%
“…While much research attention has been paid to certain forms of binegativity among plurisexual women (e.g., assumptions of promiscuity; Beach et al, 2019; Brewster & Moradi, 2010; Klesse, 2011; Schick et al, 2012; Zivony & Saguy, 2018), other forms of binegativity have not yet been as thoroughly explored. One understudied form of binegativity affecting plurisexual women is the pressure plurisexual women face to prove their plurisexuality to others with behavioral “evidence” (e.g., through sexual behavior; Flanders et al, 2017).…”
Section: Minority Stress and Plurisexual Women’s Wellbeingmentioning
confidence: 99%